Linking technological functions of fitness mobile apps with continuance usage among Chinese users: Moderating role of exercise self-efficacy - Huang, Guanxiong; Ren, Yuchen (Computers in human behavior, 2020)
Mobile apps are effective tools for administering health interventions and changing user behaviors in key lifestyle areas, such as physical activity, but the attrition rates of fitness app users are high. To understand how to increase user retention rates, the present study draws from the Technology Acceptance Model (TAM) and investigates the role of exercise self-efficacy, in addition to the original TAM constructs, namely, perceived usefulness, perceived ease of use, and perceived enjoyment, in predicting current users’ intention to continue using the apps. Moreover, this study extends TAM from a human-technology interaction perspective by elucidating the antecedents of perceived usefulness in terms of specific functions provided by fitness mobile apps. Samples were drawn from a large online Chinese subject pool to test the hypotheses via a survey (N = 449). The results showed that four technological functions—instruction provision, self-monitoring, self-regulation, and goal attainment—had an indirect effect on continuance intention through perceived usefulness, and this indirect effect was moderated by exercise self-efficacy such that the association between perceived usefulness and continuance intention was stronger for those with low exercise self-efficacy. •Four technological functions had an indirect effect on continuance intention through perceived usefulness.•This indirect effect was moderated by exercise self-efficacy.•Perceived ease of use and perceived enjoyment also predicted continuance intention.